The effect of sucrose supplements on particle-associated carboxymethylcellulase (EC 3.2.1.4) and xylanase (EC 3.2.1.8) activities in cattle given grass-silage-based diet - Huhtanen, P.; Khalili, H. (Cambridge University Press, 1992)
Carboxymethylcellulase (EC 3.2.1.4; CMCase) and xylanase(EC 3.2.1.8) activities were estimated in rumen fluid and from microbes closely associated with rumen particulate material or with feed particles incubated in nylon bags in the rumen of cattle. Cattle with a permanent rumen cannula and a simple "T"-piece duodenal cannula were given 4 diets in a 4X4 Latin Square experiment. The basal diet (diet C) consisted of grass silage, barley and rapeseed meal (700, 240 and 60 g/kg total DM) given daily or supplemented with sucrose 1.0 kg given twice daily (Diet S), twice daily with sodium bicarbonate 0.25 kg/day (diet B) or as a continuous intrarumen infusion (diet I). Giving sucrose supplements decreased CMCase and xylanase activities extracted from microbes associated with rumen particulate material or feed particles incubated in nylon bags compared with diet c. Supplementation of the sucrose diet with sodium bicarbonate resulted in higher CMCase activities than other sucrose diets (S and I). Particle-associated CMCase activities were very sensitive in detecting differences in the rumen environment and were related to changes in cell wall digestion. Activities were highly correlated with disappearance of DM and neutral-detergent fibre from nylon bags incubated in the rumen, rumen and total digestion of cell-wall carbohydrates and rumen pool size of cell-wall carbohydrates. It was concluded that the attachment of fibrinolytic enzymes is involved in the reduction fibre digestion. Particle-associated CMCase and xylanase activities were much higher when measured from rumen particulate material than from feed particles incubated in nylon bags.